Glycemic Status at Presentation and One Month after Treatment withInsulin in Gestational Diabetes Mellitus Patients Attending Tertiary LevelHospital (The Planet, 2024)
Introduction: Gestational diabetes mellitus (GDM) is a global disease that requires good glycemic control. Insulin is considered to be the most effective pharmacological management. The objective of this study is to monitor the glycemic status of gestational diabetes mellitus patients at presentation and 1 month after treatment with insulin. Methods & Materials: A prospective analytical study was done in the Endocrinology Outpatient Department of Dhaka Medical College Hospital, selected by purposive sampling from January 2022 to December 2022. Patient information was noted in a structured data collection sheet which included socio-demographic characteristics, relevant medical history, glycemic status at presentation, and 1 month after treatment with insulin. The study was analyzed using SPSS version 26.0. Result: The highest age distribution was in the 26-30 years group (41.0%), with a mean age of 27.78±4.03 years. Most patients were overweight (52.2%), followed by obese (23.1%) and normal BMI (24.6%). Regarding insulin regimens, rapid-acting insulin analog was most common (40.3%), followed by basal-bolus (35.1%). A significant association was found between insulin regimen and parity (p=0.021). Only 17.9% had a previous history of GDM, while 68.7% had no comorbidities. Glycemic control improved significantly after one month of insulin therapy, with fasting glucose, post-prandial glucose, and HbA1c levels showing marked reductions (p
Keywords: Gestational diabetes mellitus; Insulin; Glycemic Status; HbA1c